Indonesia : 2010 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Indonesia. (IMF Staff Country Reports; Country Report ;, 2010)
Indonesia's growth in 2009 was four and a half percent, the third highest in the G-20 group of countries; and the pace is accelerating in 2010. Both push and pull factors have attracted large portfolio inflows, particularly into government bonds and Short-term Bank Indonesia certificates (SBIs). The financial and corporate sectors were resilient to the crisis. They welcomed the steps being taken by the authorities to further strengthen the resilience of the financial sector in line with the recommendations of the recent Financial Sector Assessment Program (FSAP).